Operationalizing ecosystem service bundles for strategic sustainability planning: A participatory approach - Malmborg, Katja (Ambio, 2020)
The ecosystem service concept is recognized as a useful tool to support sustainability in decision-making. In this study, we collaborated with actors in the Helge å catchment, southern Sweden, in an iterative participatory ecosystem service assessment. Through workshops and interviews, we jointly decided which ecosystem services to assess and indicators to use in order to achieve a sense of ownership and a higher legitimacy of the assessment. Subsequently, we explored the landscape-level interactions between the 15 assessed services, and found that the area can be described using three distinct ecosystem service bundles. The iterative, participatory process strengthened our analysis and created a shared understanding and overview of the multifunctional landscape around Helge å among participants. Importantly, this allowed for the generated knowledge to impact local strategic sustainability planning. With this study, we illustrate how similar processes can support local decision-making for a more sustainable future. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13280-020-01378-w) contains supplementary material, which is available to authorized users.